Assessment of the Chemical Diversity and Functional Properties of Secondary Metabolites from the Marine Fungus Asteromyces cruciatus - María Paz González-Troncoso; Catalina Landeta-Salgado; Javiera Munizaga; Ruth Hornedo-Ortega; María del Carmen García-Parrilla; María Elena Lienqueo (Journal of Fungi)
Natural compounds derived from microorganisms, especially those with antioxidant and anticancer properties, are gaining attention for their potential applications in biomedical, cosmetic, and food industries. Marine fungi, such as Asteromyces cruciatus, are particularly promising due to their ability to produce bioactive metabolites through the degradation of marine algal polysaccharides. This study investigates the metabolic diversity of A. cruciatus grown on different carbon sources: glucose, Durvillaea spp., and Macrocystis pyrifera. Crude extracts of fungal biomass were analyzed for total phenolic content (TPC), antioxidant capacity (TAC), toxicity, and phenolic compound identification using ultra-high-performance liquid chromatography coupled with high-resolution electrospray ionization mass spectrometry (UHPLC-MS/MS). The analysis revealed the presence of anthraquinone compounds, including emodin (0.36 ± 0.08 mg/g DW biomass) and citrereosein in glucose medium and citrereosein and endocrocin in M. pyrifera medium. No such compounds were detected in Durvillaea spp. medium. The glucose-grown extract exhibited the highest TPC (3.09 ± 0.04 mg GAE/g DW) and TAC (39.70 ± 1.0 µmol TEq/g biomass). Additionally, no detrimental effects were observed on a neuronal cell line. These findings highlight the influence of carbon sources on the production of bioactive metabolites and their functional properties, providing valuable insights into the biotechnological potential of A. cruciatus.